Analysis of Changes in Sedimentation Volume of Kuwil Kawangkoan Reservoir with USLE Method and Area Reduction Method - Widyatama, Radya Gading; Suharyanto, Suharyanto (TEKNIK, 2025)
Sediment deposited in the reservoir will increase in line with the total erosion rate. This causes the dead storage capacity of the reservoir to siltation, so studies need to be performed to estimate the amount of erosion rate and sediment distribution during the reservoir's operational period. The study location is at the Kuwil Kawangkoan Reservoir, North Minahasa Regency, North Sulawesi Province. The study aims to determine the reservoir erosion rate using the USLE Method based on Geographic Information Systems (GIS) and to analyze changes in the reservoir sedimentation storage volume using the Area Reduction Method. Based on the analysis, the volume of sediment deposited in the Kuwil Kawangkoan Reservoir catchment area is 307,382.08 m3/tahun. Over a 50-year lifespan, the predicted total volume of settled sediment is 15.369 million m3. The results of the sediment distribution analysis indicate that after 50 years, only 17.82% of the dead storage capacity will remain. Initially, the dead storage capacity of the reservoir was 7.63 million m³, but it is projected to decrease to 1.36 million m³ at an elevation of +77.00 m, below the intake elevation. Since the intake elevation of the Kuwil Kawangkoan Reservoir is at +83.50 m, the operation of Kuwil Kawangkoan Reservoir to fulfil water demand downstream is relatively unaffected.